2007
DOI: 10.1095/biolreprod.106.057885
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Long-Term and Transgenerational Consequences of Perturbing Preimplantation Embryo Development in Mice1

Abstract: Perturbations of the development of preimplantation embryos may have long-term consequences for the health of progeny. There are no standardized methods for assessing such risks. The OECD/OCDE 416 Guideline for Testing of Chemicals (Two-Generation Reproduction Toxicity Study) is a standardized assay for detecting potential toxic effects of chemicals. The present study assessed the utility of this guideline for identifying long-term consequences of perturbing preimplantation development. Extended culturing of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 27 publications
6
37
0
1
Order By: Relevance
“…In addition, several authors re-ported modifications in adult organs size due to embryo manipulation. For instance, Mahsoudi et al [45] and Calle et al [46] observed that manipulation of preimplantation mouse embryos resulted in altered organ sizing, and Serrano et al [47] observed that modifications in embryo culture conditions modify the adult phenotypes, increasing the sensitivity to development of liver steatosis in females. These phenotypes could be the consequence of messenger RNA expression differences of metabolic relevant genes due to changes in methylation pattern [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several authors re-ported modifications in adult organs size due to embryo manipulation. For instance, Mahsoudi et al [45] and Calle et al [46] observed that manipulation of preimplantation mouse embryos resulted in altered organ sizing, and Serrano et al [47] observed that modifications in embryo culture conditions modify the adult phenotypes, increasing the sensitivity to development of liver steatosis in females. These phenotypes could be the consequence of messenger RNA expression differences of metabolic relevant genes due to changes in methylation pattern [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…The data in this study demonstrated a dose dependent effect of CH on blastocyst cell number at concentrations of peroxide that pass both the 1-cell and 2-cell group culture MEA. Since mice derived from in vitro blastocyst culture have decreased birth weight and weaning weight when compared with in vivo conceived offspring [23], this effect could be due to undetected sub-lethal doses of toxins present in the culture environment. These results highlight the need for more sensitive quality control assays.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main external factors considered to being capable of altering embryo development and affecting offspring health is the oxygen tension during culture (21). There are various animal studies suggesting that altered gene expression may take place and is majorly dependent on the IVF environment and culture media (86)(87)(88)(89)(90). Applying these data to humans is challenging and requires careful extrapolation.…”
Section: Epigeneticsmentioning
confidence: 99%